Ecology and display behaviour of breeding Eurasian woodcock Scolopax rusticola - Heward, Christopher J. (2020)
In Britain, the Eurasian woodcock Scolopax rusticola occurs as both a common winter migrant and a resident breeding species. A national Breeding Woodcock Survey, conducted in 2003, provided the first accurate assessment of Britain’s resident population size. Here, data from a second national Breeding Woodcock Survey are presented, providing the first opportunity to assess changes in abundance. I estimated Britain’s Breeding population to be 55,241 males (95% CL: 41,806–69,004), representing a 29% decline in ten years. Abundance was correlated with the availability of large, well-connected and heterogenous areas of woodland and populations have retracted towards more heavily wooded landscapes. Woodcock site occupancy increases with the availability of certain woodland types, notably birch, and with increasing distance from urban areas.